2018
DOI: 10.1123/jcsp.2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Power Improvements in Athlete and Non-Athletes During Intensive Eating Disorder Treatment

Abstract: Understanding the unique needs of athletes who undergo eating disorder (ED) treatment is sorely needed. This study explores changes of strength and power in athlete (n = 21) and non-athlete (n = 36) patients from intake to discharge. Maximal oxygen consumption, vertical jump, push-ups, hand grip strength, and body mass index (in anorexia nervosa; AN) were measured among treatment center patients. The number of push-ups and hand grip strength were significantly improved upon discharge in the full sample (ps <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…High information content determines the widespread prevalence of this criterion in studies devoted to sports and physical education. Handgrip strength is often used as an effective criterion for health-related and recreational activities [9][10][11], rehabilitation [12]. A review by Saul et al [13] is highlighted the main factors determining success in mountain climbing.…”
Section: Introductionmentioning
confidence: 99%
“…High information content determines the widespread prevalence of this criterion in studies devoted to sports and physical education. Handgrip strength is often used as an effective criterion for health-related and recreational activities [9][10][11], rehabilitation [12]. A review by Saul et al [13] is highlighted the main factors determining success in mountain climbing.…”
Section: Introductionmentioning
confidence: 99%
“…Fewell and colleagues (2018) provided an overview of a protocol for safe fitness testing and how assessments relate to ED-specific markers. In this study, Fewell and colleagues (2018) found that evaluating markers of functional stress during treatment was associated with athlete's improved confidence in their nutritional plan, acceptance of recommended weight goals, and adherence to fitness recommendations (Fewell et al, 2018).…”
Section: Sporting Considerations Performancementioning
confidence: 76%
“…Achieving peak sporting performance requires a complex interplay of physical and mental health components (El Ghoch, Soave, Calugi, & Riccardo, 2013). This requires athletes to build a positive relationship with their sport and training (Fewell et al, 2018), learn skills in effective goal setting, challenge unhelpful cognitions, and develop constructive emotional coping techniques (Conviser et al, 2018) in adjunct to achieving sport-specific fitness markers and developing a healthy relationship with food and body image. While an attitude of mental toughness and relentless pursuit of perfection is often glorified in athletes (Thompson and Sherman, 2012), a recent study demonstrated that self-compassion, not self-criticism, was positively associated with sporting performance (Killham, Mosewich, Mack, Gunnell & Ferguson, 2018).…”
Section: Sporting Considerations Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria consisted of: restricting type of AN [ 29 ]; age 12–18 years old, BMI > 14.0 (kg/m 2 ) [ 30 ], participation in regular treatment (partial outpatient regime), and enrolled within four months after admission to acute treatment. Exclusion criteria consisted of: participating in structured exercise programs, engaging in uPA, being an athlete [ 31 ], and having contraindications to perform exercise. The protocol was approved by the Ethics Committee of the hospital (ID: R-0034/08), and parental consent was obtained.…”
Section: Methodsmentioning
confidence: 99%